Penerapan Strategi Pemasaran Produk Wuling Air Ev dalam Menarik Minat Pembelian Konsumen Terhadap Mobil Listrik - Erwin Permana; Siti Khalisa Naurah Rahayu; Shifa Sabilla Hanum; Syamsurizal (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Electronic vehicles (EV) are not only an alternative for fossil fuel cars to reduce the rate of air pollution but also as a strategy to expand market share in Indonesia. This research aims to analyse the Wuling Air EV product strategy in attracting consumer to purchasing the electric cars. The research was conducted using a descriptive qualitative approach. Research data comes from search results in various digital databases and official publications. The research results show that the success of Wuling Air EV sales cannot be separated from the implementation of an omnichannel marketing strategy (offline and online) to attract consumer interest in electric vehicles. The omnichannel marketing strategy implemented involves various channels, both online or social media and directly through car shows or at dealers. This makes Wuling Motors take the opportunity, apart from intensifying promotions at dealers, offline exhibitions or car auto shows, but to utilize online marketing Wuling collaborating with car reviewers and influencers, providing options for purchasing or booking via e-commerce, and provide a home test-drive simply through the application. In this way, Wuling Indonesia has a goal of being able to create a touch point with the public regarding electronic vehicles (EV) both offline and online.